2012
DOI: 10.1155/2012/365769
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between ROS and Ras GTPases: Physiological and Pathological Implications

Abstract: The members of the RasGTPase superfamily are involved in various signaling networks responsible for fundamental cellular processes. Their activity is determined by their guanine nucleotide-bound state. Recent evidence indicates that some of these proteins may be regulated by redox agents. Reactive oxygen species (ROSs) and reactive nitrogen species (RNSs) have been historically considered pathological agents which can react with and damage many biological macromolecules including DNA, proteins, and lipids. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 93 publications
1
48
0
Order By: Relevance
“…11,20,21 In line with these studies, we observed that K-Ras V12 transforms normal fibroblasts in association with ROS generation, causing acquisition of anchorage-independent colony-forming ability and increased tumor-forming capacity. In this study, we found that K-Ras V12 -induced ROS generation occurs through NOX1.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…11,20,21 In line with these studies, we observed that K-Ras V12 transforms normal fibroblasts in association with ROS generation, causing acquisition of anchorage-independent colony-forming ability and increased tumor-forming capacity. In this study, we found that K-Ras V12 -induced ROS generation occurs through NOX1.…”
Section: Discussionsupporting
confidence: 74%
“…Also, ROS promote cancer progression by participating in oncogenic signaling pathways such as Ras, c-Myc and c-Src. [9][10][11] Indeed, Ras-induced ROS generation caused to increase the activation of mitogen-activated protein kinase (MAPK) and DNA-binding activities of the transcription factors such as activator protein-1, activator protein-2 and nuclear factor-kB in rat kidney epithelial cells, 12 suggesting that ROS participate in cell signaling.…”
mentioning
confidence: 99%
“…Moderate increases in cellular ROS levels have been shown to activate mitogenic signals (22,37,38). Many triggers of ROS have been identified including oncogenic Ras signaling which has been shown to elevate mitochondrial ROS, an important contributor for anchorage-independent growth (22).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mitogenic pathways have been directly linked to ROS (37), a process that has been co-opted by cancer cells. In oncogenic Kras driven tumors, mitochondrial-derived ROS is necessary to maintain anchorage-independent growth and modulate ERK phosphorylation to a proliferative level (22).…”
Section: Discussionmentioning
confidence: 99%
“…To trigger GPCR signal transduction in AECs, intracellular bacteria, such as Shigella , are known to engage GTPases in actin polymerization [19][20][21] . These low-molecular-weight proteins belong to the Ras GTPase superfamily and include Rab and Rho/Rac, with the ability to act as molecular switches by coupling extracellular signals to different cellular responses, cytoskeletal integrity, intracellular vesicular transport, and trafficking of proteins [22] . Inhibition of Rac1 was recently shown to repeal tumour protein p53 suppression of STAT and NF-κB, and Rho is essential in the establishment and maintenance of tight junctions [23] .…”
Section: Mycobacteria Manipulate G-proteincoupled Receptors To Increamentioning
confidence: 99%